1998
DOI: 10.1111/j.1432-2277.1998.tb00831.x
|View full text |Cite
|
Sign up to set email alerts
|

Liver conditioning after cardiac arrest: the use of normothermic recirculation in an experimental animal model

Abstract: Preliminary results of this study were presented at the XVI World Congress of the Transplantation Society, Barcelona, Spain, August 1996 J. C. Garcia Abstract The aim of this study was to compare the possible role of normothermic recirculation with the role of liver transplants from nonheart-beating donor pigs after 20 min of cardiac arrest. Three groups were studied, of which two were control groups: group 1, in which the liver was harvested from a heart-beating donor; group 2, in which the liver was harveste… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
27
0
2

Year Published

2001
2001
2019
2019

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 63 publications
(30 citation statements)
references
References 28 publications
1
27
0
2
Order By: Relevance
“…This original line of investigation revealed that normothermic extracorporeal membrane oxygenation (NECMO) could partially restore the cellular energy load lost during a period of cardiac arrest (13,14). When NECMO was compared with total body cooling after cardiac arrest, it was shown that NECMO was significantly superior in improving the histological lesion and posttransplant graft function (15,16). The beneficial effects of NECMO were demonstrated to lie in its ability to turn the initial period of cardiac arrest into one of ischemic preconditioning (17).…”
Section: Introductionmentioning
confidence: 99%
“…This original line of investigation revealed that normothermic extracorporeal membrane oxygenation (NECMO) could partially restore the cellular energy load lost during a period of cardiac arrest (13,14). When NECMO was compared with total body cooling after cardiac arrest, it was shown that NECMO was significantly superior in improving the histological lesion and posttransplant graft function (15,16). The beneficial effects of NECMO were demonstrated to lie in its ability to turn the initial period of cardiac arrest into one of ischemic preconditioning (17).…”
Section: Introductionmentioning
confidence: 99%
“…Combining chest compression with the LUCAS2 â device after death determination with nRP, Fondevila et al [23] reported the results of a series of 34 liver transplants from uDCD donors with 1-year graft and patient survival of 70% and 82% respectively. The promising results obtained with nRP can be explained by the fact that warm oxygenated reperfusion allows some repair from WIT to take place, which is supported by experimental studies [58][59][60] and allows for biochemical assessment of the liverand hence a more appropriate selection of the liver donor. It is worth noting that technical difficulties inherent to preservation with hRP/nRP may result in potential donor losses.…”
Section: Preservation Of Abdominal Organsmentioning
confidence: 92%
“…C [3,[9][10][11][12][13][14][15][16][17][18][19][20][21] (kidney) [23][24][25][26][27][57][58][59][60] (liver)…”
unclassified
“…Experimental data from our lab has shown that kidney and liver function returns and is maintained while on ECS (5). In animals, perfusing with warm oxygenated blood has been shown experimentally to increase the energy charge (ADP) and antioxidant levels in the recovered organs (6,7). By restarting circulation after cardiac arrest, the agonal, hypoxic and ischemic events surrounding death and subsequent reperfusion can be turned into an ischemic preconditioning phenomenon (8).…”
mentioning
confidence: 99%